Globalization of pharmaceutical trade and healthcare coverage of the Millennium Development Goals. Issue 1 (24th October 2019) - Yuan, Bocong; Li, Jiannan; Wang, Zhaoguo
Abstract: Objective: This study intends to empirically examine the influence of globalization of pharmaceutical trade on healthcare coverage of the Millennium Development Goals (MDGs; i.e. the measles immunization and antiretroviral therapy coverage). Method: This study uses the matched data set from World Bank and WHO during 2000–2014. The heterogeneity robust panel regression method and the fixed-effect estimation method are used to analyse the relation between globalization of pharmaceutical trade and healthcare coverage of the MDGs. Key findings: This study identifies the positive relations between globalization of pharmaceutical trade and the measles immunization coverage/ antiretroviral therapy coverage. Conclusion: The globalization of pharmaceutical trade can help achieve healthcare coverage of the MDGs, especially for countries under the resource-constrained condition.